Social Plasticity Relies on Different Neuroplasticity Mechanisms across the Brain Social Decision-Making Network in Zebrafish - Teles, Magda C.; Cardoso, Sara D.; Oliveira, Rui F. (Frontiers in Behavioral Neuroscience, 2016)
Social living animals need to adjust the expression of their behavior to their status within the group and to changes in social context and this ability (social plasticity) has an impact on their Darwinian fitness. At the proximate level social plasticity must rely on neuroplasticity in the brain social decision-making network (SDMN) that underlies the expression of social behavior, such that the same neural circuit may underlie the expression of different behaviors depending on social context. Here we tested this hypothesis in zebrafish by characterizing the gene expression response in the SDMN to changes in social status of a set of genes involved in different types of neural plasticity: bdnf, involved in changes in synaptic strength; npas4, involved in contextual learning and dependent establishment of GABAergic synapses; neuroligins (nlgn1 and nlgn2) as synaptogenesis markers; and genes involved in adult neurogenesis (wnt3 and neurod). Four social phenotypes were experimentally induced: Winners and Losers of a real-opponent interaction; Mirror-fighters, that fight their own image in a mirror and thus do not experience a change in social status despite the expression of aggressive behavior; and non-interacting fish, which were used as a reference group. Our results show that each social phenotype (i.e. Winners, Losers and Mirror-fighters) present specific patterns of gene expression across the SDMN, and that different neuroplasticity genes are differentially expressed in different nodes of the network (e.g. BDNF in the dorsolateral telencephalon, which is a putative teleost homologue of the mammalian hippocampus). Winners expressed unique patterns of gene co-expression across the SDMN, whereas in Losers and Mirror-fighters the co-expression patterns were similar in the dorsal regions of the telencephalon and in the supracommissural nucleus of the ventral telencephalic area, but differents in the remaining regions of the ventral telencephalon. These results indicate that social plasticity relies on multiple neuroplasticity mechanisms across the SDMN, and that there is not a single neuromolecular module underlying this type of behavioural flexibility.